Improving Sme Accountability In The M-Wallet Era Postadoption Implications - Tri Puspita Sari; Nurna Aziza (UNIVED Press, 2024)
This research aims to investigate the impact of M-Wallet adoption on SME financial accountability and its implications for small and medium business practices. The research method uses a mixed approach which combines qualitative (interviews) and quantitative (questionnaire) approaches. The population in this study is UKM in Bengkulu that have adopted M-Wallet in operations. The sampling technique uses survey techniques. Data collection techniques used interviews and questionnaires with a Linkert scale of 1-5. Data testing uses multiple linear regression analysis. Based on the research results, it can be concluded that there has been an increase in SME accountability in the mwallet era with post-adoption implications. The regression results show that system security influences SME accountability. SMEs feel that a high level of system security can reduce the risk of data loss or financial theft, thereby increasing accountability in managing finances. The regression results show that system effectiveness influences SME accountability. The effectiveness of the system in processing transactions more quickly, providing financial reports that are easy to understand, and providing good visibility into cash flow has a role in improving accountability practices.